Usage of Metaheuristics in Engineering: A Literature Review - (:unkn) unknown (IGI GLOBAL, 2013)
A metaheuristic is conventionally described as an iterative generation process which guides a servient heuristic by combining intelligently different concepts for exploring and exploiting the search space, learning strategies are used to structure information in order to find efficiently near-optimal solutions. In the literature, usage of metaheuristic in engineering problems is increasing in a rapid manner. In this study; a survey of the most important metaheuristics from a conceptual point of view is given. Background knowledge for each metaheuristics is presented. The publications are classified with respect to the used metaheuristic techniques and application areas. Advantages and disadvantages of metaheuristics can be found in this chapter. Future directions of metaheuristics are also mentioned.
Keywords: ANT-COLONY OPTIMIZATION; PARTICLE SWARM OPTIMIZATION; SIMULATED-ANNEALING ALGORITHM; ARTIFICIAL NEURAL-NETWORK; VEHICLE-ROUTING PROBLEM; TRAVELING SALESMAN PROBLEM; TABU SEARCH ALGORITHM; FACILITY LAYOUT PROBLEM; GENETIC ALGORITHM; DIFFERENTIAL EVOLUTION